2008
DOI: 10.1002/ajmg.a.32366
|View full text |Cite
|
Sign up to set email alerts
|

A new look at XXYY syndrome: Medical and psychological features

Abstract: XXYY syndrome occurs in approximately 1:18,000-1:40,000 males. Although the physical phenotype is similar to 47,XXY (tall stature, hypergonadotropic hypogonadism, and infertility), XXYY is associated with additional medical problems and more significant neurodevelopmental and psychological features. We report on the results of a cross-sectional, multicenter study of 95 males age 1-55 with XXYY syndrome (mean age 14.9 years), describing diagnosis, physical features, medical problems, medications, and psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
210
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(228 citation statements)
references
References 56 publications
13
210
1
4
Order By: Relevance
“…Recent studies have shown that, compared with males in the general population, males with Klinefelter syndrome report more distress during specific social situations and are characterized by increased levels of autistic features across all dimensions of the autism phenotype. Recently, Tartaglia et al 57 reported a prevalence of ASDs among individuals with XXYY syndrome of 28.3 ⁄ 100 and showed that neurodevelopmental and psychological difficulties were a significant component of the behavioural phenotype, with developmental delay and learning disability universal but variable in severity.…”
Section: Klinefelter Syndromementioning
confidence: 99%
“…Recent studies have shown that, compared with males in the general population, males with Klinefelter syndrome report more distress during specific social situations and are characterized by increased levels of autistic features across all dimensions of the autism phenotype. Recently, Tartaglia et al 57 reported a prevalence of ASDs among individuals with XXYY syndrome of 28.3 ⁄ 100 and showed that neurodevelopmental and psychological difficulties were a significant component of the behavioural phenotype, with developmental delay and learning disability universal but variable in severity.…”
Section: Klinefelter Syndromementioning
confidence: 99%
“…The abnormal functioning of the dopaminergic and serotonergic systems (5, 7-9), among other neurotransmitters, were repeatedly found in ADHD and ASD, and therefore the candidate genes common for both disorders are the dopaminergic transporter gene, dopaminergic receptor type 3 and type 4 genes, serotonin transporter gene, and genes for catechol-o-methyl-transferase and monoamine oxidase type A (4), although genome-wide association studies did not confirm with certainty all these candidates (10). A shared genetic basis is further suggested by the higher frequency of ADHD and ASD traits in children with a defined genetic diagnosis such as 22q11 deletion syndrome, XXYY syndrome, and microdeletions or duplications in the chromosome 15q13.2-q13.3 region (11,12). However, the molecular agents related to various biological processes and interactions between different risk factors responsible for development of ADHD and ASD remain elusive (6).…”
Section: Attention-deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%
“…They may have behavioral problems such as impulsivity, hyperactivity and bouts of agitation [6]. While there are case reports on medical and psychological problems in patients with XXYY syndrome [14], the literature is limited in regard to their problematic sexual behavior. Through this case report we present sexual behavior in a patient of XXYY syndrome, such as: exhibitionism, voyeurism, fellatio and cunnilingus.…”
Section: Case Discussionmentioning
confidence: 99%
“…Males with XXYY syndrome often have speech-language disorders, social-emotional difficulties, cognitive impairments, poor visualperceptual skills and are also more likely to have hyperactive/ impulsive symptoms [4]. The major indication for chromosomal analysis has been mental retardation and behavioral problems, like violent and impulsive reactions [6,[13][14][15]. There have been case reports of children with XXYY presenting with suicidal ideation and aggressive behavior with presumable diagnosis of mixed bipolar episode [16].…”
Section: Review Of Literaturementioning
confidence: 99%